Temperature Estimation with Deep Learning Methods: The Example of Diyarbakir Province - Sevinç, Aynur; Kaya, Buket (Ali KARCI, 2021)
Short-term temperature forecasts are required in many applications. The demand for such forecasts has increased in many fields, especially in the energy industry. Data-driven models for better temperature predictions are gaining more and more popularity. These approaches include deep learning concepts, namely neural networks with multiple hidden layers. The focus of this study is to demonstrate the feasibility of deep learning for air temperature prediction based on meteorological data. In this context, T.C. Using the air temperature data between the years 2014-2020 taken from the Meteorological Data Information Presentation and Sales System (MEVBIS) of the General Directorate of Meteorology, temperature forecasts were made with deep learning algorithms for the province of Diyarbakir, located in the Southeastern Anatolia Region. The deep learning architecture of this study is long-short term memory (LSTM), which is a special type of recursive neural networks (RNN). In addition, the analysis was made with the Automatic Regressive Integrated Moving Average (ARIMA) model used in forecasting studies in this study and successful results were obtained. Long Short Term Memories (LSTM) networks from deep learning algorithms are frequently used to predict temperature, wind speed or radiation. After the system was trained, the R-square score value was found to be 0.96. This parameter value is a criterion showing that air temperature prediction values very close to the actual air temperature values are obtained. The accuracy of the prediction provided by our ARIMA and LSTM model is both appropriate and satisfactory. It has been determined that the temperature predictions made by these methods perform well and can be used successfully in air temperature prediction.

Birçok uygulamada kısa vadeli sıcaklık tahminleri gereklidir. Bu tür tahminlere olan talep birçok alanla beraber özellikle enerji endüstrisinde artmıştır. Daha iyi sıcaklık tahminleri için veriye dayalı modeller giderek daha fazla popülerlik kazanmaktadır. Bu yaklaşımlar arasında derin öğrenme kavramları, yani birden çok gizli katmana sahip sinir ağları bulunmaktadır. Bu çalışmanın odak noktası, meteorolojik verilere dayalı hava sıcaklığı tahmini için derin öğrenmenin uygulanabilirliğini göstermektir. Bu kapsamda T.C. Meteoroloji Genel Müdürlüğü Meteorolojik Veri Bilgi Sunum ve Satış Sistemi’nden (MEVBİS) alınan 2014-2020 yılları arasındaki hava sıcaklığı verileri kullanılarak, Güneydoğu Anadolu Bölgesi’nde yer alan Diyarbakır ili için derin öğrenme algoritmaları ile sıcaklık tahmini yapılmıştır. Bu çalışmanın derin öğrenme mimarisini, Özyinelemeli Sinir Ağlarının (Recurrent Neural Network-RNN) özel bir türü olan Uzun-Kısa Süreli Bellek (Long-Short Term Memory-LSTM) oluşturmaktadır. Ayrıca bu çalışmada tahmin çalışmalarında kullanılan Otomatik Regresif Entegre Hareketli Ortalama (ARIMA) modeli ile de analiz yapılmış ve başarılı sonuçlar ortaya çıkmıştır. Derin öğrenme algoritmalarından LSTM ağları sıcaklığı, rüzgar hızını veya radyasyonu tahmin etmek için sıklıkla kullanılmaktadır. Sistem eğitildikten sonra R-kare skoru değeri 0.96 olarak bulunmuştur. Bu parametre değeri, gerçek hava sıcaklığı değerlerine çok yakın hava sıcaklığı tahmin değerleri elde edildiğini gösteren bir kriterdir. ARIMA ve LSTM modelimizin sağladığı tahminin doğruluğu hem uygun hem de tatmin edicidir. Bu yöntemlerle yapılan sıcaklık tahminlerinin iyi performans gösterdiği ve hava sıcaklığı tahmininde başarılı bir şekilde kullanılabileceği tespit edilmiştir.
Derin Öğrenme Yöntemleri ile Sıcaklık Tahmini: Diyarbakır İli Örneği
Keywords: Artificial Intelligence; Yapay Zeka